The World is (Ge-)Mine. The Speculative Life of the sensus communis with Arendt and Hegel - Akin, Zanan (HannahArendt.net, 2025)
By determining sensus communis as the “sensation of reality,” Hannah Arendt invites us to take its sense character literally. If it is a sense, like the other senses, sensus communis must be vulnerable to blockage, disturbance, and even loss. This article argues that this vulnerability cannot be captured within an epistemological framework of “objective knowledge”, because what is today at stake is the object itself, namely the world as an in-between. The question thus is whether there is a common world at all—i.e. whether the world appears as a political space. To pursue this question, I mobilize the speculative potential of the prefix Ge- in German Gemeinsinn: the word’s internal tension between two poles, namely gemein as “common” and as “mean”, points to a passing over of common into the privatized Ge-mein (“mine”) that turns mistrust into the only – perverted – common sense today. The title “The World is (Ge-)Mine” names this dynamic: the world is shared, yet it becomes deceptive and unhomely where it is gathered as the mere availability of what each ‘I’ appropriates as its own. Reading Arendt along a diagonal to Hegel, I show that the realness of the world is neither a natural faculty nor a transcendental guarantee but an affirmative creation—ultimately bound to what Arendt calls the “supreme capacity of men”: the capacity for beginning.